Tragal perichondrium as graft material in tympanoplasty: our experience - Pathak, Vivek K.; Nayak, Pradeepti; Tyagi, Sonali; Chaudhary, Rohit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: It has been defined as a permanent abnormality of pars tensa or flaccida, as a result of acute otitis media, negative middle ear pressure or otitis media with effusion. It manifests clinically as ear discharge and decreased hearing and may lead to numerous changes in the tympanic membrane, middle ear cleft, and mastoid air cell system. It has been classified into two types: mucosal and squamosal types. Chronic otitis media (COM) is a very common condition in developing countries in both adult and paediatric age groups. This study has been conducted to determine the outcome and graft uptake of tragal perichondrium in type 1 tympanoplasty. Methods: The prospective analytical study was conducted department of otorhinolaryngology, School of Medical Sciences and Research, Greater Noida, Uttar Pradesh, India over a period of 12months from 01 January 2019 to 31 December 2019. 30 patients according to inclusion criterion underwent tympanolpasty using tragal perichondrium were included in study. The data obtained was analyzed using statistical package for the social sciences (SPSS), version 21.0. P value less than 0.05 was taken as statically significant. Results: Preoperative mean hearing loss was 38.45±7.01 dB, mean air bone gap was 20.20±3.75 dB, and postoperative air bone gap was reduced to an average of 10.86±3.82 dB. 8.51 dB of hearing gain was achieved and an air bone gap réduction of 8.51 dB was observed. Conclusions: Our study concluded tragal perichondrium is a suitable graft material is n mucosal type of COM.